2006
DOI: 10.1142/s0218127406016938
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dynamical Systems Using Symbolic Images: Efficient Implementation and Applications

Abstract: Symbolic images represent a unified framework to apply several methods for the investigation of dynamical systems both discrete and continuous in time. By transforming the system flow into a graph, they allow it to formulate investigation methods as graph algorithms. Several kinds of stable and unstable return trajectories can be localized on this graph as well as attractors, their basins and connecting orbits. Extensions of the framework allow, e.g. the calculation of the Morse spectrum and verification of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…On the other hand, when it is associated with cycles of a high period, the period doubling bifurcations of the two cycles occur almost simultaneously, so that the effect can be numerically observed, but it is difficult to detect the related period. 1 We thank Soumitro Banerjee for this figure. Clearly the node becomes a saddle, and an attracting node of double period C 2N appears, with periodic points on both sides of the unstable manifold issuing from C N . Similarly for the saddle, a second branch becomes unstable, and a saddle of double period C 2S appears, with periodic points on both sides of the unstable manifold issuing from C S .…”
Section: Real Eigenvaluesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, when it is associated with cycles of a high period, the period doubling bifurcations of the two cycles occur almost simultaneously, so that the effect can be numerically observed, but it is difficult to detect the related period. 1 We thank Soumitro Banerjee for this figure. Clearly the node becomes a saddle, and an attracting node of double period C 2N appears, with periodic points on both sides of the unstable manifold issuing from C N . Similarly for the saddle, a second branch becomes unstable, and a saddle of double period C 2S appears, with periodic points on both sides of the unstable manifold issuing from C S .…”
Section: Real Eigenvaluesmentioning
confidence: 99%
“…In several applied models (see, e.g., [1,[3][4][5]) it has been observed that closed invariant curves in three dimensional (3D for short) maps can undergo a kind of doubling bifurcation sequence. The bifurcation mechanism leading to such a dynamic behavior was announced as an open problem at the European Conference on Iteration Theory in 2006 (ECIT-06) [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unstable cycles are detected by the variant of the cell-to-cell mapping method 14,15 described in Ref. 16. Multiplier q of the fixed point is calculated by Eq.…”
Section: Boundary Of the Stability Domain Of Fixed Pointsmentioning
confidence: 99%
“…The symbolic image G is a directed graph such that vertex i corresponds to the cell M (i) and the edge i → j exists if f (M (i))∩M (j) = ∅. The notion of symbolic image of a dynamical system was introduced in 1983 [9], monograph [10] and paper [1] describe the symbolic image methods and their applications. We will use symbolic image construction with respect to a partition C. In general case, there are no any restrictions on properties of cells.…”
mentioning
confidence: 99%